Paradoxes of organizational change in a merger context - Cunha, M. P.; Neves, P.; Clegg, S. R.; Costa, S.; Rego, J. (Qualitative Research in Organizations and Management, 2019)
Purpose: The reorganization of the Portuguese national healthcare system around networks of hospital centers was advanced for reasons promoted as those of effectiveness and efficiency and initially presented as an opportunity for organizational transcendence through synergy. The purpose of this paper is to study transcendence as felt by the authors’ participants to create knowledge about the process. Design/methodology/approach: The paper consists of an inductive approach aimed at exploring the lived experience of transcendence. The authors collected data via interviews, observations, informal conversations and archival data, in order and followed the logic of grounded theory to build theory on transcendence as process. Findings: Transcendence, however, failed to deliver its promise; consequently, the positive vision inscribed in it was subsequently re-inscribed in the system as another lost opportunity, contributing to an already unfolding vicious circle of mistrust and cynicism. The study contributes to the literature on organizational paradoxes and its effects on the reproduction of vicious circles. Practical implications: The search for efficiency and effectiveness through strategies of transcendence often entails managing paradoxical tensions. Social implications: The case was researched during the global financial crisis, which as austerity gripped the southern Eurozone gave rise to governmental decisions aimed at improving the efficiency of organizational healthcare resources. There was a sequence of advances and retreats in decision making at the governmental level that gave rise to mistrust and cynicism at operational levels (organizations, teams and individuals). One consequence of increasing cynicism at lower levels was that as further direction for change came from higher levels it became interpreted in practice as just another turn in a vicious circle of failed reform. Originality/value: The authors contribute to the organizational literature on paradoxes by empirically researching a themes that has been well theorized (Smith and Lewis, 2011) but less researched empirically. The authors followed the process in vivo, as it unfolded in the context of complex strategic change at multiple centers.